Global city-region ambition in the Netherlands: From Randstad to Deltametropolis - Bart Lambregts (European Regional Science Association (ERSA), 2002)
The recent renaming of the Dutch Randstad into 'DeltaMetropolis' can be seen as part of a broader strategy to capitalise upon the region's metropolitan and economic potentials and to strengthen its international competitive position. This strategy was first presented by the national planning authorities at the end of the 1980s as a key element of spatial policy in the Fourth National Memorandum on Spatial Planning and it is now prolonged in the recently launched Fifth National Memorandum on Spatial Planning (Fifth Memorandum). An essential difference with 15 years ago is the fact that the current policy strategy for the Randstad is the result of a clear 'give-and-go' between Randstad-based local and regional stakeholders on the one hand and the national (planning) authorities on the other. At the end of the 1990s, local and regional stakeholders in the Randstad joined forces in a broad coalition (which is still growing) to pursue the objective of developing the Randstad into a metropolitan entity named 'DeltaMetropolis'. By turning this highly urbanised region into a thinly populated metropolis a better position in the international inter-urban and inter-regional competitive arena was (and is) aspired to. While this objective fit in with the broad strategy followed by the national government, the DeltaMetropolis coalition had to lobby hard during the preparatory stages of the Fifth Memorandum to make sure that the Randstad in the same document was conceptualised as a single urban network rather than three or four separate 'network cities'. The lobby succeeded and even the long-standing name of the Randstad was traded in for the new name proposed by the coalition. With these developments, which may also be judged as the Randstad having become the subject of a project involving the 'establishment' of the region as an actor in a wider (political) context, the region seems to qualify increasingly well as an illustrative case for the recently presented global city-region thesis (Scott et al., 2001). This thesis expands upon the global city thesis by combining important elements from both the 'new regionalism' school and the 'Los Angeles' approach to urban and regional economics. It stresses the growing importance of so-called 'global city-regions' as both political actors and regional economic motors in the emerging global economy as the result of a wide range of forces of political, technological and economical origin. The aim of the present paper is mainly to explore the extent to which recent developments regarding the Randstad/DeltaMetropolis are indeed compatible with the global city-region thesis (both in political and economic terms). The paper presents a summary of the global city-region thesis and a brief outline of recent developments regarding the Randstad/DeltaMetropolis. In addition, an analysis of the (potential) qualities of the Randstad/DeltaMetropolis as a political actor and a regional economic motor is presented. In conclusion some instructive elements are derived from the global city-region thesis for the DeltaMetropolis project. Reference: Scott, A.J., J. Agnew, E.W. Soja and M. Storper (2001) Global City-Regions, in: A.J. Scott (ed.) Global City-Regions: Trends, Theory, Policy, pp. 11-32. Oxford: Oxford University Press.
Keywords: 330